Adjacent, distal, or combination of point-selective effects of acupuncture on temporomandibular joint disorders: A randomized, single-blind, assessor-blind controlled trial - Kyung-Won Kang; Woo-Young Kim; Tae-Hun Kim; Byung-Cheul Shin; So-Young Jung; Ae-Ran Kim; Sun-Mi Choi (Integrative Medicine Research, 2012)
Background: The objectives of this study were to compare the efficacy of acupuncture among different types and to evaluate point-selective pain relief effects between selected adjacent or distant points in participants with temporomandibular joint disorders (TMDs). Methods: Forty-two participants were randomly allocated to three groups: an adjacent point selection group (Trt, n = 14), a distant point selection group (Con1, n = 14), or a combination group (Con2, n = 14). All three groups received a total of six acupuncture sessions (twice a week for 3 weeks), the outcomes being assessed pain intensity using a 10-cm visual analogue scale, and the palpation index of the muscle and temporomandibular joint every week of treatment and 4 weeks after the end of treatment. Results: The pain intensity was reduced in the Trt (34%), Con1 (31%), and Con2 (36%) groups after 3 weeks compared with each group's baseline, with no significant difference among the three groups (p = 0.5867). Similarly, the palpation index was decreased by 52% (Trt), 62% (Con1), and 50% (Con2) after 3 weeks of treatment, but no significant differences between groups were shown (p = 0.3289). Conclusion: Our results suggest that point-selective effects among adjacent, distal, or a combination of acupoints are hardly associated with pain intensity or palpation index in participants with TMDs. Larger sample size trials are required to overcome the shortcomings of the study.